Manuscript of Hikayat Hang Tuah (PNM: MSS 1713): a study of decorative binding and its meaning / Azlini Anuar Tan and Mumtaz Mokhtar - Anuar Tan, Azlini; Mokhtar, Mumtaz (Universiti Teknologi MARA, Kedah, 2020)
This concept paper attempts to investigate the history of Islamic binding from the point of view of binding structure and decoration motifs in Hikayat Hang Tuah manuscript (PNM: MSS 1713). In this study, binding is defined as a mechanised process of physically folding a sheet of folio. Partially, the process involves folding the sheets together into a number of sections and turning into a codex. In addition to this, the ancient manuscript is written by hand with ink. Also, the association materials in the making of Islamic manuscript used with appropriate organic materials. The difference between western and Islamic binding involves the type of styles, materials and techniques used in the binding. Unlike binding from western style, the style of Islamic binding is influenced by the Arabic world tradition and follows the Islamic principle. The art decoration is inspired by the great dynasty during the Ottoman, Safavid and Mughal era. Generally, the decoration in the Islamic art involves organic motifs, geometry, calligraphy and abstracts. On this subject, one of the famous Malay folktales in Malay World is Hikayat Hang Tuah. In other words, Hikayat Hang Tuah manuscript is the scientific study of the manuscript, the primary examination was mainly focused on the binding structure, materials, technique, and illumination. This is followed by the problem statement which emphasises the diversity of decoration on the form and contents in the Hikayat Hang Tuah, as well as to make comparisons between the manuscripts produced in the east coast of the Malay Peninsula. The aim of this research is to investigate the history of Malay binding from the point of view of its binding structure and its decoration motifs in Hikayat Hang Tuah manuscript (PNM: MSS 1713). It also aims to uncover the philosophical message and its meaning. The methodology used in the analysis was the qualitative methods. The method used in this research varies. The main method is associated with conservation procedure. This procedure involved an examination of the leather, observation on the paper, sampling and sample preparation on the hand-sewn and analysis characteristic on the illumination. Besides, information is received from the library such as journals, books and articles. Other aids in the field study are delivery information from different sources, interviews from the point of geographically and historically perspectives. This research will reveal the significant differences in the origins of the motifs and design elements represented in the Malay world, based on visual and technical arrangements found in the Hikayat Hang Tuah manuscript. Furthermore, the influence of this analysis will serve as a scholarly reference for the comparative and critical analysis from tradition motifs leading into innovative creation from traditional craftwork.